Influence of Internal Domestic Relations and Traditions on Efficiency of Moral Education of Rising GenerationThe Еssence of the Тechnology of Сase-Method in the Рrofessional Тeachersʼ Тraining - Kovalova, Svitlana (Pedagogical Discourse, 2015)
The article deals with the essence of the technology of case-method. The definition of categorical apparatus of this method and its basic concepts such as a case, the case method, case-study, case-portfolio, situational training, problem situation and its direct relevance to the professional teachersʼ training are analyzed. In the article the technology of case-method of professional staff training is proposed, the ground of the terminology on the problem is carried out. It is noted that the basic concepts are interrelated and directly related to the training of teachers, so they require some clarification. The special attention is paid to the features and technological features that distinguish case-method from other teaching methods during the work with cases. The essential features of the method of situational learning, which is a collective understanding of a situation in terms of certain tasks are examined. It is determined that case-method consists of a case study, which involves consideration of complex conflict cases, problematic situations, incidents in the process of learning. In conclusion it is necessary to say that the work with cases in the classroom allows to apply theoretical knowledge to solve practical problems, helps to develop studentsʼ independent thinking, linking theory with practice. The work with cases is creative and is a determiner of the high level of teaching. It has been discovered that case-method creates a positive motivation for the successful knowledge digestion and personalityʼs activity.